Dielectric properties of 0-3 lead magnesium iobate titanate (PMT)-ordinary Portland Cement (PC) composites - Nittaya Jaitanong (2018)
The dielectric properties of lead magnesium niobate titanate, PMNT and portland cement, PC with x(0.67PMN-0.33PT)-(1-x)(PC) (where x = 0.3, 0.5, 0.7 and 1.0) composites were investigated. The dielectric properties of the 0-3 PMNT-PC composites are measured as function of both room temperatures and frequency. The composites were pressed together and cured in 98%RH curing chamber for 3 days before measurements. The results indicate that the dielectric properties of the PMNT-PC composites increased with increasing PMNT content with dielectric constant, εr obtained for the composites with 0.3, 0.5 and 0.7PMNT with dielectric constant, εr values of a 136, 414 and 647 respectively. © (2010) Trans Tech Publications, Switzerland.